Evaluation of the Implementation of a Local Wisdom-Based Primary School Literacy Programme in Central Lombok - Gazali, Munawir; Ningsih, Dewi Puspita (Primary Journal of Multidisciplinary Research, 2025)
Literacy at the primary school level constitutes a fundamental foundation for 21st-century learning and should ideally be integrated into learners’ socio-cultural contexts. This study is grounded in the urgency of strengthening literacy based on local wisdom as a strategy for character development, cultural literacy, and sustainability, particularly within the context of Sasak culture in Central Lombok (Hemayati & Susilawati, 2020; Lailiya et al., 2025; Jubaedah et al., 2025). The study aims to evaluate the implementation, effectiveness, challenges, and best practices of a local wisdom-based primary school literacy programme in Central Lombok. This research employs an evaluative design using a mixed-methods approach based on the CIPP model. The research participants comprised primary school teachers, principals, and students from several districts in Central Lombok. Data were collected through classroom observations, in-depth interviews, questionnaires, focus group discussions, and programme document analysis. Data analysis was conducted using thematic qualitative analysis and descriptive quantitative techniques, referring to an integrative approach to curriculum development based on local knowledge (da Silva et al., 2023; Hikmah Syafiulia et al., 2025a; Muyassaroh et al., 2024). The findings indicate that the integration of Sasak folklore, oral traditions, and local socio-religious values into literacy activities significantly enhances students’ reading interest, cultural understanding, and character development, in line with previous studies on cultural literacy (Li et al., 2025; Beasley, 2023; Dewi, 2020; Sa’diyah & Dewi, 2023). However, the programme implementation still faces challenges, including the limited availability of local teaching materials, varying levels of teacher readiness, and inconsistent school-level policy support (Negussie et al., 2018; Syahrizal, 2025; Veliz et al., 2025). This study recommends strengthening teacher capacity, increasing the provision of local learning resources, and fostering the systemic integration of local wisdom-based literacy within an ethnopedagogical school culture (Hikmah Syafiulia et al., 2025b; Winursiti et al., 2012; Yazidi & Rijal, 2024).